The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1109/tkde.2010.188
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Helpfulness and Economic Impact of Product Reviews: Mining Text and Reviewer Characteristics

Abstract: Abstract-With the rapid growth of the Internet, the ability of users to create and publish content has created active electronic communities that provide a wealth of product information. However, the high volume of reviews that are typically published for a single product makes harder for individuals as well as manufacturers to locate the best reviews and understand the true underlying quality of a product. In this paper, we re-examine the impact of reviews on economic outcomes like product sales and see how d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
810
7
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,082 publications
(851 citation statements)
references
References 46 publications
26
810
7
8
Order By: Relevance
“…For instance, Amazon.com provides a service that displays the top two most helpful, favourable, and critical reviews posted by online users in order to help its customers evaluate each displayed product easily. These useful votes are generally believed not only to be an indicator of review diagnosticity to separate the useful reviews from the rest (Mudambi & Schuff, 2010), but also to be a signalling cue for users to filter numerous reviews efficiently (Ghose & Ipeirotis, 2008). In other words, the useful information in a review may assist customers to evaluate the attributes of the service so as to build confidence in the source (Gupta & Harris, 2010).…”
Section: Perceived Usefulness Of Online Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Amazon.com provides a service that displays the top two most helpful, favourable, and critical reviews posted by online users in order to help its customers evaluate each displayed product easily. These useful votes are generally believed not only to be an indicator of review diagnosticity to separate the useful reviews from the rest (Mudambi & Schuff, 2010), but also to be a signalling cue for users to filter numerous reviews efficiently (Ghose & Ipeirotis, 2008). In other words, the useful information in a review may assist customers to evaluate the attributes of the service so as to build confidence in the source (Gupta & Harris, 2010).…”
Section: Perceived Usefulness Of Online Reviewsmentioning
confidence: 99%
“…To be more specific, the dependent variable is online review usefulness (PU) measured by counting the number of online users who voted that the reviews were useful in response to the reviews posted (Ghose & Ipeirotis, 2010;Jin, Lu & Shi, 2002). The independent variables, including the messenger's name, address, and real photo, are binary variables to be measured as '1' if they disclose information and '0' otherwise.…”
Section: Operationalization Of Data Variablesmentioning
confidence: 99%
“…In a context in which evaluation objects are ideas represented through text, the readability of that text is critical, as readability has been defined as the ease of understanding or comprehension of text due to the style of writing (Klare 1963). Readability relates directly to the cognitive effort of understanding text (Ghose and Ipeirotis 2011). Existing research has shown that readability strongly influences human decision processes.…”
Section: Readability Of Ideasmentioning
confidence: 99%
“…Existing research has shown that readability strongly influences human decision processes. For instance, Ghose and Ipeirotis (2011) show that higher readability of user-generated online reviews positively influences purchase decisions. Similarly, Tan et al (2014) found that readability moderates the effect between the presentation of financial reports and the investors' earning evaluations.…”
Section: Readability Of Ideasmentioning
confidence: 99%
See 1 more Smart Citation